The relationship between socio-demographic factors, parental attachment and the level of health literacy awareness and practice among Malaysian adolescents - Hamzah, Siti Raba'ah; Suandi, Turiman; Ismail, Maimunah (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
This is a cross-sectional study was conducted to determine the relationship between the sociodemographic factors, parental attachment and the level of health literacy awareness and practice among Malaysian adolescents. Data were collected on a sample of 506 adolescents aged 15-17 years. The research instrument used was a self-administered questionnaire comprising of items eliciting information on health literacy (pertaining to awareness and practice), socio demographic factors and parental attachment. The results showed the level of health literacy awareness among Malaysian adolescents was moderate (M=3.55, SD=0.54) and the level of health literacy practice was high (M=3.69, SD=0.56). The study also revealed health literacy was influenced by gender, ethnicity, place of residence, household income and parental attachment. The study demonstrates there is a relationship between socio-demographic factors, parental attachment and the level of health literacy awareness and practice, thus to enhance the level of health literacy among adolescents, the government and other agencies related to health care should ensure demographic factors and parental attachment are taken into account when dealing with health literacy among adolescents.